Peroxisome proliferator activated receptor α (PPARα) and PPAR gamma coactivator (PGC-1α) induce carnitine palmitoyltransferase IA (CPT-1A) via independent gene elements - Song, Shulan (2010)
Long chain fatty acids and pharmacologic ligands for the peroxisome proliferator activated receptor alpha (PPARα) activate expression of genes involved in fatty acid and glucose oxidation including carnitine palmitoyltransferase-1A (CPT-1A) and pyruvate dehydrogenase kinase 4 (PDK4). CPT-1A catalyzes the transfer of long chain fatty acids from acyl-CoA to carnitine for translocation across the mitochondrial membranes and is an initiating step in the mitochondrial oxidation of long chain fatty acids. PDK4 phosphorylates and inhibits the pyruvate dehydrogenase complex (PDC) which catalyzes the conversion of pyruvate to acetyl-CoA in the glucose oxidation pathway. The activity of CPT-1A is modulated both by transcriptional changes as well as by malonyl-CoA inhibition. In the liver, CPT-1A and PDK4 gene expression are induced by starvation, high fat diets and PPARα ligands. Here, we characterized a binding site for PPARα in the second intron of the rat CPT-1A gene. Our studies indicated that WY14643 and long chain fatty acids induce CPT-1A gene expression through this element. In addition, we found that mutation of the PPARα binding site reduced the expression of CPT-1A-luciferase vectors in the liver of fasted rats. We had demonstrated previously that CPT-1A was stimulated by the peroxisome proliferator activated receptor gamma coactivator (PGC-1α) via sequences in the first intron of the rat CPT-1A gene. Surprisingly, PGC-1α did not enhance CPT-1A transcription through the PPARα binding site in the second intron. Following knockdown of PGC-1α with short hairpin RNA, the CPT-1A and PDK4 genes remained responsive to WY14643. Overall, our studies indicated that PPARα and PGC-1α stimulate transcription of the CPT-1A gene through different regions of the CPT-1A gene.